PERANCANGAN KONSEP DAN LAYOUT APLIKASI BERBASIS WEBSITE E-CANTEEN UPN VETERAN JAWA TIMUR - I Desak Made Aprilia Anggraeni Pradanti; Widyasari Widyasari; Diana Aqidatun Nisa (Jurnal Nawala Visual, 2023)
The canteen is a place that we often encounter in various locations, one of which is in educational institutions such as campuses or universities. One of them is the East Java UPN Veterans canteen called "Warung NKRI". According to research results, this canteen has several problems related to the efficiency of the buying and selling transaction process. Existing problems have their own impact on the smooth teaching and learning process. Therefore the authors designed an application based on the e-canteen website to overcome the problems that exist in the UPN Veteran East Java canteen. The design chosen by the author was obtained from research results and adapted to current developments, namely the era of the industrial revolution 4.0. Where everything related to life undergoes a digitalization process. The type of application used in this design was chosen based on the results of the author's research, where the research results show that website-based applications are in accordance with the target audience of this design. In this design, we discuss how the author designed the concept and layout for the UPN Veterans East Java e-canteen application.